The Influence of Positive Affirmations on the Self-Efficacy of Students Who Will Undertake Nursing Clinical Practice in Hospitals - Desy Rinawaty; Nadhifah Rahmawati; Andi Satriana (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Nursing students are students who study nursing. Nursing students who will carry out clinical practice activities are required to have readiness both conceptually, psychomotorically, and attitudinally. This research aims to show the effect of positive affirmation to self-efficacy of students who will carry out clinical nursing practice in hospitals. The sample used was 20 STIKes Kendedes students, Callisto class, using total sampling techniques. This research used Quasy Experimental and using one group pre test post test design as the design. The results showed that self-efficacy before positive affirmation was carried out, some respondents had moderate self-efficacy, while self-efficacy after positive affirmation was carried out, it was found that most respondents had high efficacy. Wilcoxon analysis show that the result with p-value was 0.000 <0.05, which mean that positive affirmation influential to self-efficacy of students who will carry out clinical nursing practice in hospitals.